Prophetic Leadership Scale’s Validation and the Tendency of Normative Response - Fida Tazkiyah; Helli Ihsan; Muhammad Ariez Musthofa (Jurnal Psikologi Islam dan Budaya, 2020)
This study aims to validate the prophetic leadership scale by using a quantitative approach. 202 leaders were involved in this study. Data analysis technique that has been used for construct validation is factorial validation with confirmatory factor analysis (CFA), a convergent validation, discriminant validation, and social desirability bias with Pearson correlation. There are 4 instruments used in this study, namely the measuring instrument of prophetic leadership, the measuring instrument of authentic leadership as a convergent validator, the measuring instrument of religiosity as a discriminant validator, and the measuring tool of social desirability as a validator of social appropriateness bias. The prophetic leadership measurement tool measures the same construct as the authentic leadership measurement tool, and measures different constructs from the religiosity measurement tool, and the prophetic leadership measurement tool has a social appropriateness bias or the respondent's tendency to give answers in accordance with norms. The findings raise a prospect that social desirability bias’s influences fitness indices in a scale’s validation.